(E)-N′-(3,4-Dimethoxybenzylidene)nicotinohydrazide monohydrate - Novina, J. Josephine (International Union of Crystallography, 2014)
In the title hydrated compound, C(15)H(15)N(3)O(3)·H(2)O, the nicotinohydrazide molecule adopts a trans conformation with respect to the C=N double bond. The dihedral angle between the benzene and pyridine rings is 5.10 (14)°. In the crystal, the solvent water molecule acts as an acceptor, forming an N—H⋯O hydrogen bond supported by two C—H⋯O contacts. It also acts as a donor, forming bifurcated O—H⋯(O,O) and O—H⋯N hydrogen bonds that combine with the former contacts to form zigzag chains of molecules along the c-axis direction. An additional O—H⋯O donor contact completes a set of six hydrogen bonds to and from the water molecule and connects it to a third nicotinohydrazide molecule. This latter contact combines with weaker C—H⋯O hydrogen bonds supported by a C—H⋯π contact to stack molecules along b in a three-dimensional network.